3D MODELING COMPUTATION TO EVALUATE GROYNE STRUCTURE PERFORMANCE: CASE STUDY OF PASSO COASTAL AREA - Salamena, Ganisa Elsina; Salamena, Gianita Anastasia; Loupatty, Grace; Palembang, Citra Fathia (PATTIMURA UNIVERSITY, 2025)
Groyne is very important to protect the coastline with the concept of maintaining the balance of sediment transport. Groyne building in theory can work well if worked in groups or more than one. In this study, the Passo beach location was chosen because there is an existing groyne building that, if seen on Google Earth, has been damaged by the scattering of the constituent rocks. If the groyne cannot work to balance the sediment transport, it may occur that mass destruction to the infrastructure behind the groyne itself, such as regional roads, may occur. To find out the level of damage, an in-depth study needs to be carried out. In this paper, Delft-3D mathematical modeling was carried out to investigate groyne damage by looking at the performance of groyne in maintaining the balance of sediment transport in the Passo beach area. Hydrodynamic and coastal sediment modeling analyses were carried out in wet and dry season conditions. Modeling was carried out over one month with a morphology factor of 12 to obtain sediment transport for one year. In the existing dry season conditions, it shows that at the observation point, there is erosion of 2 meters, and in the wet season sediment transport is balanced. It is implied that the groyne structure must be replaced for being surpass the structure lifetime.